Democracia e gestão pública participativa : um estudo do orçamento participativo de Niterói (RJ) - Gonçalves, Tatiana dos Santos (2010)
This thesis object is to analyze the management mechanisms and the political organization of the Participative Budget (PB) in Niterói city, Rio de Janeiro, between 1997 and June of 2008. Therefore, interviews with seven managers, manager delegates, also called PB coordinators and three PB counsels were done. The interviews analysis used four analysis categories: 1)Rights and citizenship access 2)The PB s answer capacity; 3)PB s management; and 4)Political context of the Participative Budget implementation. This management mechanisms analysis allows the comprehension about the democratic potential of Niterói s PB, that is, the possibilities to construct a democratic public field which is built with the actors incorporation in the political community and with the interference power in the decisive process.